URGENSI LITERASI SERTIFIKASI HALAL BAGI USAHA KECIL MENENGAH (UKM) DI KABUPATEN NGAWI - Lina Nur Anisa (Investama : Jurnal Ekonomi dan Bisnis, 2022)
This paper has the goal of providing knowledge, understanding, and assistance related to the urgency of halal certification to Usaha Kecil Menengah (UKM), especially in the Ngawi district; providing insight related to the effect of halal certification on product buyer satisfaction; forming business prospects; and also forming experience related to the stages in applying for halal certification at LPPOM MUI through the CEROL online service. With increased insight and experience, it can increase the productivity and competitiveness of UKM in Ngawi district. On the other hand, it can also increase the area of the positive multiplier effect in the areas with the most UKM activists. The implementation of the companion activities is carried out from the socialization stage to accompanying the process of registering halal product guarantee certification online for UKM players who are engaged in the culinary field. Through the assistance of the halal certification process, problems related to how to apply for a halal certificate are considered difficult to solve and become the first example for other UKM in the Ngawi district.